2003
DOI: 10.1034/j.1398-9995.2003.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

The control of asthma in Italy. A multicentre descriptive study on young adults with doctor diagnosed current asthma

Abstract: Despite the high percentage of drug users, the control of symptoms and exacerbations was overall poor in Italy and resulted in a heavy individual and social burden, pointing out that the guideline goals have far from been reached in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 36 publications
8
56
0
4
Order By: Relevance
“…However, 59% of patients were studied during their first specialist visit, immediately after referral from a GP, and data gathered on that occasion probably reflect the level of care provided by GPs. Moreover, a recent population-based survey showed that the majority of Italian asthma patients are in the care of specialists rather than GPs, and, more importantly, that the ratio of GP-treated to specialist-treated patients is consistent across the levels of asthma control [32]. This scenario may be different from other healthcare environments and could be explained by the cost structure of the Italian health service, which facilitates access to specialists by patients across the entire disease spectrum.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, 59% of patients were studied during their first specialist visit, immediately after referral from a GP, and data gathered on that occasion probably reflect the level of care provided by GPs. Moreover, a recent population-based survey showed that the majority of Italian asthma patients are in the care of specialists rather than GPs, and, more importantly, that the ratio of GP-treated to specialist-treated patients is consistent across the levels of asthma control [32]. This scenario may be different from other healthcare environments and could be explained by the cost structure of the Italian health service, which facilitates access to specialists by patients across the entire disease spectrum.…”
Section: Discussionmentioning
confidence: 72%
“…This was designed to minimise erroneous inclusion of patients with COPD, the prevalence of which increases with age [31]. Although this is a broader age limit than was selected for other similar studies [14,32], most retired persons and those with serious comorbidity, who might also have left the workforce, were excluded. This selection may inflate the present overall estimate of indirect costs per patient by over-representing adult asthma patients who are still in the active work force.…”
Section: Discussionmentioning
confidence: 99%
“…The ISAYA was a multicentre, cross-sectional survey of the young adult population, specifically aimed at assessing the variations of asthma and the current management of asthmatics in Italy [15][16][17]. The survey was carried out between 1998 and 2000 in nine Italian centres, of these six were in northern Italy (Udine, Pavia, Turin, Verona, Sassuolo, and Ferrara), and three were in central/southern Italy (Pisa, Sassari and Siracusa).…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Despite the availability of several ICS/LABA combination therapies, many patients in the real world have suboptimal asthma control [6,7]. This may reflect the presence of practical and physical…”
Section: Introductionmentioning
confidence: 99%